Dialek Bahasa Madura Pada Masyarakat Pendalungan Di Desa Tanggul Wetan, Kecamatan Tanggul - Yessy putri Wulandari; Fitri Sakinah; Callista Azalia Nur Firdaus; Hasan Suaedi (An Nafi': Multidisciplinary Science, 2025)
The Madurese dialect used by the people of Tanggul Wetan village, Tanggul sub-district, represents the fusion of Madurese and Javanese cultures in multiethnic life. This study aims to identify the characteristics and significance of the dialect as part of the cultural identity of the Pendalungan community. A descriptive qualitative approach is used through observation and interviews to examine language use in different social contexts. The results showed that the Madurese dialect in this village has unique characteristics in the form of a mixture of vocabulary, intonation and grammar influenced by Javanese culture. This dialect is not only a means of communication, but also a symbol of identity and solidarity of the local community. It also serves as a medium for the preservation of traditions, such as the transmission of folklore, customs and social values that reflect respect, courtesy and openness to diversity. In the face of the challenges of globalisation, these dialects demonstrate the community's ability to adapt without losing its cultural roots. This study confirms the importance of local dialect preservation as an effort to maintain local cultural wealth and community identity in the face of global cultural homogenisation.